Gestión de ventas en la “automotriz Suárez” ubicada en el cantón Vinces, periodo 2022-2023 - Muñoz Aspiazu, Cinthya Lorena (2023)
In this case study, an analysis of the sales management carried out in the “Automotriz Suárez” located in the Vinces canton will be carried out, to determine what deficiencies are that prevent an adequate positioning for the company. “Automotriz Suárez” is a business that is dedicated to the purchase and sale of spare parts and provides vehicle maintenance, repair and washing services in which the following problems arise: little recognition, poor use of advertising and sales strategies, The personnel who work in the sales area do not have technical knowledge and the increase in competition. Through this research, the owner of the automotive company and her sales team will be able to identify the points where it is necessary to apply improvement actions and determine the most appropriate strategies to implement. The selected method that was implemented was the root cause analysis, along with the survey technique applied to the sales force to know their degree of training and the SWOT analysis, which allowed knowing the current situation of the business through its internal and external factors. Through the data collection instruments applied, it was possible to evaluate the sales management carried out in the automotive company and reach the conclusion that it is not efficient, because the staff has little technical training and there is little application of promotion and sales strategies. Reasons why it was recommended to develop a marketing campaign that highlights your strengths and key differentiators, implement training programs for your sales staff and apply promotion strategies and sales strategy such as: content marketing, loyalty programs, strategic alliances , promotions and attractive discounts to improve the positioning of the business.